The knife before Christmas - Carlisle, Kate, 1951- (Carlisle, Kate, 1951- Fixer-upper mystery, 2024)
"Contractor Shannon Hammer hopes for a peaceful Christmas with her fiancé, Mac, until murder throws a wrench in her holiday plans in a brand-new installment of the USA Today bestselling Fixer-Upper Mystery Series. Christmas has come to Lighthouse Cove, but business hasn't slowed down for Shannon Hammer. She's been contracted to renovate a local hotel owned by the Garrisons, a family that's so devoted to the holidays they serve a seven-course dinner every night from Thanksgiving through Christmas. Last year's festivities featured a train that transported guests around the breathtaking Cliffside property. This year, Shannon and her crew have been commissioned to build a Victorian-style carnival midway with games and prizes galore. Everyone in town loves the hotel's spirit, except the Garrisons' children and their spouses, who are hum-bugged by the money being wasted on holiday cheer while their inheritance goes up the chimney. Things turn nasty when a mischief-maker close to the family is found dead. It's up to Shannon and Mac to catch a sinister Scrooge before all of Lighthouse Cove receives coal for Christmas"--